Does Boardroom Ethnic Diversity Shape ESG Performance? Insights from the US Banking Sector - Varouchas, Evangelos G.; Arvanitis, Stavros E.; Agiomirgianakis, George M.; Floros, Christos (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
This research investigates the relationship between ethnic diversity in the boardroom and the ESG performance of US banks during the 2016-2021 period. To this aim, we implement the 2-step system GMM estimation technique, which addresses endogeneity issues that have posed challenges in many studies. Our findings indicate that boardroom ethnic diversity negatively influences ESG performance. Moreover, in a nonlinear analysis, we provide evidence of a U-shaped relationship between boardroom ethnic diversity and the ESG performance of banks. These results remain robust when, instead of ESG performance, we examine the social and corporate governance performance of banks. We also demonstrate that the impact of boardroom ethnic heterogeneity on ESG performance varies with bank size. Furthermore, we reveal that during the pandemic, the previously negative impact of ethnically diverse directors on ESG performance shifts and ultimately becomes positive. Consequently, our conclusions serve as an important source of information to lawmakers and regulators and enrich the corporate governance research concerning the nexus between board characteristics and ESG performance.